2022
DOI: 10.3390/biom12020279
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of Matrix Metalloproteinase and Sepsis: The Need Speed Study

Abstract: Many causal mechanisms in sepsis susceptibility are largely unknown and the functional genetic polymorphisms (GP) of matrix metalloproteinases (MMPs) and their natural tissue inhibitor of MMPs (TIMP1) could play a role in its development. GPs of MMPs and TIMP (namely MMP-1 rs1799750, MMP-3 rs3025058, MMP-8 rs11225395, MMP-9 rs2234681, and TIMP-1 rs4898) have been compared in 1058 patients with suspected sepsis to assess the association with susceptibility and etiology of sepsis. Prevalence of MMP8 rs11225395 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Thus, the vascular wall gets damaged and the microvessels become more permeable, increasing the likelihood of sepsis [23] . Previous research shows that Intracellular pathogens, viruses, and fungi have been shown to induce the expression of host MMPs, implying that MMPs may be a potential therapeutic target in sepsis, which is consistent with our results [24] . The diagnostic value of MMP9 in sepsis has also been previously reported [25,26] .…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the vascular wall gets damaged and the microvessels become more permeable, increasing the likelihood of sepsis [23] . Previous research shows that Intracellular pathogens, viruses, and fungi have been shown to induce the expression of host MMPs, implying that MMPs may be a potential therapeutic target in sepsis, which is consistent with our results [24] . The diagnostic value of MMP9 in sepsis has also been previously reported [25,26] .…”
Section: Discussionsupporting
confidence: 93%
“…59,60 Dysregulation of MMP3 contributes to the pathogenesis of liver disease, 61 and similar to Fractalkine, MMP3 is implicated as a critical regulator of infection. [62][63][64][65] Inappropriately elevated MMP3 has both prognostic implications as a biomarker of sepsisrelated mortality and mechanistic importance in the pathogenesis of sepsis-related acute respiratory distress syndrome (ARDS) and multi-system organ failure. 66,67 The immunologic consequences of chronic HCV infection have been well studied, and it is known to not only induce chronic in ammation, but also signi cantly impact immune function.…”
Section: Discussionmentioning
confidence: 99%
“…71,72 Dysregulation of MMP3 contributes to liver disease pathogenesis, 73 and similar to Fractalkine, MMP3 is a critical regulator of infection. [74][75][76][77] Inappropriately elevated MMP3 is both a biomarker of sepsis-related mortality and a mediator of damage in sepsis-related multi-system organ failure. 78,79 The immunologic consequences of chronic HCV infection have been well studied.…”
Section: Discussionmentioning
confidence: 99%